Hot corrosion behavior of CYSZ thermal barrier coating with optimized laser surface modification - Avci, Ali; Karabas, Muhammet; Eker, Aysegul Akdogan; Akman, Erhan; Aslan, Caner (ELSEVIER SCI LTD, 2023)
The current study aims to investigate the influence of laser surface modification on the hot corrosion, fracture toughness, and hardness resistance of atmospheric plasma sprayed Ceria-Yttria Stabilized Zirconia (CYSZ) thermal barrier coating. Throughout the laser surface modification process, a variety of laser processing parameters are used to obtain the finest surface properties and optimum laser parameters. In this study, the whole coating surface is modified using the optimal parameters. The results show that 52.9 W laser power at a 220 mm laser distance and a 60 mm/s scanning speed were found as the optimum laser glazing parameters. A hot corrosion test is performed in a box furnace for 20 h at 1050 degrees C. Scanning electron microscopy (SEM) images show denser surfaces in laser-glazed coatings when compared to air-spraying coatings. A dense microstructure combined with the top coat is created in the coating cross-section, and a smooth microstructure with a coaxial fracture network is produced on the surface. The laser-glazed layer has superior mechanical characteristics to the as-sprayed coating, including hardness and fracture toughness. This layer also restricts the damaging monoclinictetragonal phase change for CYSZ TBC, blocking the infiltration of molten salt. The hot corrosion behavior of TBCs is improved by the inclusion of a dense laser-glazed layer.
Keywords: Thermal barrier coating; Plasma spray; Laser glazing; Hot corrosion; PLASMA-SPRAYED CERIA; RESISTANCE; YSZ; Materials Science